A collaborative machine tool maintenance planning system based on content management technologies - Wan, Shan; Li, Dongbo; Gao, James X.; Roy, Rajkumar; He, Fei (Springer, 2016)
From product maintenance and service point of view, high-value sophisticated computer numerical control (CNC) machine tools in modern manufacturing factories play important roles: they are manufacturing equipment, and on the other hand, they are also products supplied by equipment manufacturers. There is a trend that manufacturers are extending their responsibilities to the products use phase to meet customers’ requirements for lifetime support and service. To ensure the effective performance and efficient maintenance of high-value machine tools, information and knowledge from their lifecycle should be collected and reused. However, in the research area of product service systems and related computerised maintenance systems, there is a lack of research work on how to integrate knowledge from different stakeholders into the maintenance and service planning process, which is important for modern digital manufacturing systems to reduce machine tools’ downtime and improve their working performance. This project proposed a collaborative maintenance planning framework to connect different stakeholders and integrate their knowledge into the maintenance and service process. The potential of advanced content management systems (CMSs), which are widely used non-engineering sectors such as finance, business, publishing and government organisations, has been explored and tested for applications in the manufacturing engineering domain. The research realised that CMSs have several advantages compared with traditional engineering information systems, especially in managing dynamic and unstructured knowledge. A prototype maintenance and service planning system has been developed and evaluated using a real CNC machine tool.
Keywords: Product service system; Content management system; Knowledge management; Process management; Machine tool maintenance and service